The Influence Of Marketing Strategy On Consumer Purchasing Decisions At Transcom Megatronik, Gunungsitoli City - Budiwati Halawa; Otanius Laia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of the study was to determine the effect of marketing strategies on consumer purchasing decisions and to determine how much influence marketing strategies have on consumer purchasing decisions at Transcom Megatronik, Gunungsitoli City. The type of research used in this study is quantitative research. So the sample in this study was 36 people, this sampling was 36 because there were 36 consumers at Transcom. Data collection techniques used observation, questionnaires and documentation. Based on the results of the study conducted by the researcher, it was found that the Marketing Strategy at Transcom Megatronik, Gunungsitoli City was still not optimal and needed to be improved in order to attract product purchasing decisions at Transcom Megatronik, Gunungsitoli City. From the observations made by the author throughout the study, the author saw that consumers did not really know the products that would be sold because the marketing strategy was not optimal. And from the results of the study, the author concluded that the better the marketing strategy at Transcom Megatronik, Gunungsitoli City, the more purchasing decisions at Transcom Megatronik, Gunungsitoli City.